2012
DOI: 10.5152/eajm.2012.04
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopic Approach to Quadrigeminal Cistern Arachnoid Cysts

Abstract: Objective: The introduction of neuroendoscopy has provided a minimally invasive modality for the surgical treatment of quadrigeminal arachnoid cysts. Three pediatric patients with arachnoid cyst of the quadrigeminal cistern treated by endoscopic fenestration are reported. Materials and Methods:The hospital records of patients were retrospectively rewieved. All patients had hydrocephalus. A lateral ventricle-cystostomy and endoscopic third ventriculostomy were performed by using rigid neuroendoscopes.Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Interhemispheric arachnoid cysts are usually unilateral, midline, or parasagittal, away from ventricles, and usually not causing hydrocephalus [4]. Quadrigeminal cistern cysts are uncommon but usually compress the cerebral aqueduct at an early stage, presenting with hydrocephalus when symptomatic, and their treatment is imperative [5]. Arachnoid cysts located in the middle cranial fossa (approximately 50-65% of related cases) can be classified with the Galassi classification: type I cysts are small and usually asymptomatic, with anterior middle cranial fossa location; type II cysts are located superiorly along the Sylvian fissure displacing the temporal lobe; and type III cysts, like the case described, are exceptionally large, being able to take up the entire middle cranial fossa, displacing the temporal, parietal, and frontal lobes [6].…”
Section: Discussionmentioning
confidence: 99%
“…Interhemispheric arachnoid cysts are usually unilateral, midline, or parasagittal, away from ventricles, and usually not causing hydrocephalus [4]. Quadrigeminal cistern cysts are uncommon but usually compress the cerebral aqueduct at an early stage, presenting with hydrocephalus when symptomatic, and their treatment is imperative [5]. Arachnoid cysts located in the middle cranial fossa (approximately 50-65% of related cases) can be classified with the Galassi classification: type I cysts are small and usually asymptomatic, with anterior middle cranial fossa location; type II cysts are located superiorly along the Sylvian fissure displacing the temporal lobe; and type III cysts, like the case described, are exceptionally large, being able to take up the entire middle cranial fossa, displacing the temporal, parietal, and frontal lobes [6].…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, hydrocephalus is the most common presentation observed on the majority of studies [20][21][22][23], and signs of intracranial hypertension such as headache, drowsiness, bulging fontanel, visual impairment, and macrocrania have been frequently reported [20]. Ideally, the goal of surgery is to restore the pathway of the CSF by performing fenestrations on the cyst wall that communicate to the normal subarachnoid space, ventricle, and other cisterns [19,24]. Alternatively, a diverting shunt could be inserted into the cyst to reduce the internal pressure and consequently the compression of the surroundings, even with an augmented risk of failure [21].…”
Section: Rationale Of Treatmentmentioning
confidence: 99%
“…[56] Due to their close proximity to the pineal quadrigeminal neurovascular structures, quadrigeminal cysts should undergo minimally invasive treatment. [57] Endoscopic treatment of quadrigeminal cysts has yielded good results, with shunt independency rates ranging from 78% to 92.9%. [58,59] In addition, Cinalli et al found that VC combined with ETV for quadrigeminal cysts leads to better outcomes than VC alone.…”
Section: Intracranial Cystsmentioning
confidence: 99%